Peran Motivasi Belajar Dalam Meningkatkan Prestasi Belajar Siswa Kelas 4 Di Sekolah Dasar Muhammadiyah - Subhan Adi Santoso (DIDAKTIKA, 2024)
Individuals learn existence (stimulus) from the outside world and possibly patterns from within because there are dynamic principles within each individual. The following are the dynamic aspects of this person: Goal seeking, mind, and drive: Goal seeking is the process by which an individual's behavior is focused on achieving certain goals; mind is a qualitative substance distinct from physical, and drive is the individual's internal driving force, more generally referred to as "motive." The method used in data collection is descriptive method. While the approach taken is a quantitative approach. Data collection in this study includes literature study and field study. The implementation of this field study involves observation techniques, interviews, and using data collection instruments in the form of questionnaires. Based on the results of correlation analysis obtained 0,538. In order for this number to be meaningful, it needs to be interpreted so as to give an explanation of the correlation between learning motivation and student achievement, that is by consulting through the value of r on the product moment table, either with a significance level of 5% or 1%. For more details will be interpreted r o and r t (table) as follows. At the level of significance of 5% with the number of respondents (N) = 22 obtained r t = 0.423, while r o = 0.538. Thus r o is greater than r t or in other words r o> r t. This means indicating a significant or positive correlation between the two variables. At the level of significance of 1% with the number of respondents (N) = 22 obtained r t = 0.537, while r o = 0.538. Thus r o is greater than r t or in other words r o> r t. This means indicating a significant or positive correlation between the two variables. So the hypothesis examined that "There is a significant correlation between learning motivation and learning achievement subjects grade 4 students in SD Muhammadiyah Gresik.